Study on Optimum Condition of Empty Fruit Bunch (EFB) Based Superabsorbent Polymer Composite - Siti Aisyah, Shamshun Baharin (2013)
This research presents an upgrade of superabsorbent polymer composite (SPC) towards water absorbency by adding a fibre using empty fruit bunch (EFB). The scope of this study was to determine the optimum condition of EFB based SPC when the filler, crosslinker and initiator amount being varied and also the effect of water absorbency towards different pH solution. The technique used was solution polymerization. The SPC were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscopy (FESEM) and Thermo Gravimetric Analysis (TGA). Optimum water absorbency were achieved at 119.64 g/g at 25wt%, 129.005 g/g at 20wt% and 144.778 g/g at 5wt% for the initator, crosslinker and empty fruit bunch amount, respectively. Optimum condition of water absorbency was found to be in alkaline solution which is at pH 8 for initiator content, pH 10 for crosslinker concentration and pH 8 for filler content.